The narration of the experience by the elder Terena: reflections from Walter Benjamin - Ventura, Lidnei; Vilarim, Paulo (Seven Editora, 2023)
Based on the role of narrativity in the sharing of ancestral experiences, the present work starts from Walter Benjamin’s conception of narration, identifying the ancient of the Terena ethnic group, from Mato Grosso do Sul, as the exemplar of the classic narrator. From this perspective, the ancient is taken as the authority of a time traveler, whose role in the community is to repress the immemorial experience [Erfharung] of his people, to preserve them and transmit them to new generations. The work is based on fragments of narratives by teachers from Terena indigenous schools collected by one of the researchers. These fragments are taken as small Benjaminian monads, from which complex illuminations of meanings radiate on the experiences [Erlebnis] of the Terena people and their struggle of resistance against the shattering of their traditions and ways of life. Thus, the objective is to reflect on the fundamental role played by the Terena ancient in the conservation of archaic narrativity, which has the following characteristics: practical sense, authority in the preservation of tradition and guardian of the memory and wisdom of the native peoples, brushing the relevance of these guardians against the grain. DOI: 10.56238/pacfdnsv1-065